Just in case - Viorst, Judith. frey50; Bluthenthal, Diana Cain (New York : Atheneum Books for Young Readers, 2006)
Charlie likes to be ready for anything, imagining that his house could be flooded or a mermaid might kidnap him, but he learns that it is sometimes good to be unprepared. Annotation. Charlie is a boy who is always ready for anything...just in case. What if it's raining very hard -- so hard that rain could come into the house and make the furniture float? Charlie has a plan to keep himself dry...just in case. What if his parents are going out and he gets a babysitter who won't read to him or let him watch TV? Charlie has a plan for making his own fun...just in case. Charlie likes to be ready for anything. But as Charlie is about to find out, sometimes not being ready is even better.
"Ginee Seo books."
Ages 3-7.
A Junior Library Guild selection.
87489
Keywords: Preparedness -- Fiction; Preparedness -- Juvenile fiction